Study on the Use of a Variety of Plastic Materials in a Mixture of High Density Polyethylene (HDPE) in a Mixture Based on Wear AC-WC Layers (Asphalt Concrete Wearing Course) - Suprayitno Suprayitno; Sri Wiwoho Mudjanarko (LPPM of NAROTAMA UNIVERSITY, 2019)
Roads with flexible pavement are pavements that use asphalt as an aggregate binder, so they are much in demand rather than rigid pavement. Road infrastructure requires maintenance whose conditions must be maintained on an ongoing basis. The use of plastic packaging cannot be separated in everyday life. HDPE (High density polyethylene) is high density polyethylene. Based on the problem of the amount of used plastic waste currently available, this research is needed to find out how well the pavement uses the use of HDPE (High Density Polyethylene) plastic as mixed plastic waste. After testing the laboratory and analyzing it according to the General Highway Specifications for normal composition 1 without a mixture of 0%, the asphalt content that meets all the requirements is estimated at asphalt level between 5.6% - 6%. Whereas in composition 2-4 with HPDE plastic waste 4%, 8%, and 12%. From the results of the research with 4 different compositions, it is obtained that the optimal asphalt content composition of HDPE plastic mixture is 0-12% which meets the VIM and stability an optimal 8% HDPE plastic mixture was obtained with an optimum asphalt content of 4.45%